Comparison of Ultrasound-Guided Thoracic Paravertebral Block Versus Thoracic Paravertebral Block Combined With Serratus Anterior Plane Block or Erector Spinae Block Following Video-Assisted Thoracoscopic Lobectomy - Zheng MM; Xie J; Tan W; Yuan CW; Qi DY; Sun J (Therapeutics and Clinical Risk Management)
Meng-Meng Zheng,1,* Jue Xie,1,* Wei Tan,2 Cong-Wang Yuan,1 Dun-Yi Qi,3 Jie Sun1,* 1Department of Anesthesiology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, People’s Republic of China; 2Department of Anesthesiology, Yancheng Third People’s Hospital, Yancheng, People’s Republic of China; 3Department of Anesthesiology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Sun, Department of Anesthesiology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, 210009, People’s Republic of China, Email dgsunjie@hotmail.comPurpose: Compared the efficacy of ultrasound-guided thoracic paravertebral block (TPVB) and thoracic paravertebral combined with serratus anterior plane block (SAPB) or erector spinae block (ESPB) following video-assisted thoracoscopic lobectomy(VATL).Patients and Methods: This retrospective study analyzed the medical records of 295 patients who underwent VATL surgery between August 2021 and January 2023. Patients were divided into three groups: TPVB (92 patients), TPVB combined with SAPB (106 patients), and TPVB combined with ESPB (97 patients). The primary outcomes were postoperative pain levels, measured using an 11-point visual analogue scale (VAS) both at rest and during coughing at 2, 6, 12, 24, and 48 hours postoperatively, as well as cumulative oxycodone consumption within 24 and 48 hours postoperatively.Results: Postoperative cumulative oxycodone consumption within 24 and 48 hours was significantly lower in the TPVB+SAPB and TPVB+ESPB groups compared to the TPVB group (P < 0.001), with no significant difference between the TPVB+SAPB and TPVB+ESPB groups. The TPVB group exhibited higher VAS pain scores both at rest and during coughing at 2 and 6 hours postoperatively compared to the other two groups (P < 0.005). Within 24 hours postoperatively, the Area Under Curve (AUC) for VAS scores at rest was significantly lower in the TPVB+SAPB group than in the other two groups (P < 0.05), while the AUC for coughing pain was significantly lower in the TPVB+ESPB group compared to the TPVB group (P = 0.049). Nausea or vomiting occurred more frequently in the TPVB group compared to the other groups (P = 0.016).Conclusion: TPVB combined with SAPB or ESPB provides superior analgesic effects compared to TPVB alone after video-assisted thoracoscopic lobectomy, with both techniques showing comparable analgesic efficacy. However, TPVB+SAPB may offer slightly better analgesia at rest, while TPVB+ESPB may have a potential advantage in reducing postoperative nausea and vomiting.Keywords: thoracic paravertebral block, TPVB, serratus anterior plane block, SAPB, erector spinae plane block, ESPB, video-assisted thoracoscopic lobectomy, VATL, postoperative analgesia